Age-dependent association of clonal hematopoiesis with COVID-19 mortality in patients over 60 years - Marta Del Pozo-Valero; Marta Corton; Rosario López-Rodríguez; Ignacio Mahillo-Fernández; Javier Ruiz-Hornillos; Pablo Minguez; Cristina Villaverde; María Elena Pérez-Tomás; María Barreda-Sánchez; Esther Mancebo; Lidia Fernández-Caballero; Ruth Fernández Sanchez; et al. (GeroScience, 2023)
Clonal hematopoiesis, especially that of indeterminate potential (CHIP), has been associated with age-related diseases, such as those contributing to a more severe COVID-19. Four studies have attempted to associate CHIP with COVID-19 severity without conclusive findings. In the present work, we explore the association between CHIP and COVID-19 mortality. Genomic DNA extracted from peripheral blood of COVID-19 patients ( n = 241 deceased, n = 239 survivors) was sequenced with the Myeloid Solutions™ panel of SOPHiA Genetics. The association between clonality and age and clonality and mortality was studied using logistic regression models adjusted for sex, ethnicity, and comorbidities. The association with mortality was performed with patients stratified into four groups of age according to the quartiles of the distribution: 60–74 years, 75–84 years, 85–91 years, and 92–101 years. Clonality was found in 38% of the cohort. The presence of CHIP variants, but not the number, significantly increased with age in the entire cohort of COVID-19 patients, as well as in the group of survivors ( p < 0.001). When patients were stratified by age and the analysis adjusted, CHIP classified as pathogenic/likely pathogenic was significantly more represented in deceased patients compared with survivors in the group of 75–84 years (34.6% vs 13.7%, p = 0.020). We confirmed the well-established linear relationship between age and clonality in the cohort of COVID-19 patients and found a significant association between pathogenic/likely pathogenic CHIP and mortality in patients from 75 to 84 years that needs to be further validated.